Temperature-induced metal-insulator transition in a non-symmetric Hubbard model at half-ﬁlling - Didukh, L.; Hankevych, V. (Condensed Matter Physics, 1999)
In the present paper metal-to-insulator transition with the increase of temperature is studied in a narrow-band model with non-equivalent Hubbard subbands at half-ﬁlling. It is shown that the results obtained in the considered model are essentially distinct from those obtained in the Hubbard model. The results are applied to the interpretation of some experimental data.